Clinical Features and Risk Factors for Outcome in Hemodialysis Patients with COVID-19 after Complete Liberalization of Epidemic Control in China - Shuang Zhang; Shu-Xin Liu; Zhi-Hong Wang; Ping Xiao; Hong Liu; Yan Lu; Cui Dong; Lian-Lian You (Karger Publishers, 2024)
Introduction: Patients undergoing hemodialysis (HD) are highly vulnerable during the COVID-19 pandemic. We aimed to investigate the risk factors associated with the severity of COVID-19 and death after the complete liberalization of epidemic control in China. Methods: We followed the outcomes of the HD patients of Central Hospital of Dalian University of Technology, from December 6, 2022, to January 8, 2023. The non-contrast-enhanced chest computed tomography (CT) was performed on all COVID-19-infected hospitalized patients. We recorded the patient's clinical characteristics, demographic features, vaccination history, treatments, and lung lesions. Odds ratios and 95% confidence intervals were calculated using logistic regression models to identify independent risk factors for COVID-19-related severity and mortality. Results: This study included a total of 858 HD patients, of which 660 were infected with COVID-19. The mean age was (55.61 ± 14.61) years, with a median (interquartile range) dialysis duration of 44.5 (69.5) months. Over half (60%) of the study participants were male, and the majority had hypertension as a comorbidity. Multivariable analysis revealed that age, pre-dialysis diastolic pressure, fever, white blood cell (WBC) count, potassium, β2-microglobulin level, and calcium were independent risk factors for disease severity, while platelets, urea nitrogen, serum chlorine and creatinine were identified as independent protective factors. Furthermore, total iron-binding capacity and vaccination were found to be independent protective factors against mortality, and WBC count was an independent risk factor for in-hospital mortality (p < 0.05). The most frequent CT finding among hospitalized patients with chest symptoms was patchy shadow or pleural effusion, observed in 64.8% of cases. More than half of the patients exhibited bilateral lung lesions, and over 60% involved two or more lobes. Conclusion: The majority of HD patients are susceptible to COVID-19. Demographic, clinical features, and laboratory indicators can be used to predict the severity and mortality associated with COVID-19. Our findings will assist clinicians in identifying markers for the early detection of high mortality risk in HD patients with COVID-19.